2005
DOI: 10.1097/01.coc.0000170583.42741.cd
|View full text |Cite
|
Sign up to set email alerts
|

Biweekly Administration of Cisplatin/Gemcitabine in Advanced Nonsmall Cell Lung Cancer

Abstract: The schedule of cisplatin and gemcitabine analyzed is active with a good therapeutic index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…It should be stressed that this was an unplanned analysis, subjective to biases and, therefore, this finding can only be considered as 'hypothesis generating'. Finally, the mild toxicity profile of DD-GC, similarly to the results of the only other study using biweekly gemcitabine at 2500 mg/m 2 combined with 50 mg/m 2 of cisplatin in NSCLC patients [14], indicates that higher gemcitabine doses could be safely used. Biweekly gemcitabine at doses of up to 3000 mg/m 2 has been used in combination with other agents, such as capecitabine, paclitaxel and vinorelbine [15,21,26].…”
Section: Treatment Details and Toxicity Analysissupporting
confidence: 57%
See 2 more Smart Citations
“…It should be stressed that this was an unplanned analysis, subjective to biases and, therefore, this finding can only be considered as 'hypothesis generating'. Finally, the mild toxicity profile of DD-GC, similarly to the results of the only other study using biweekly gemcitabine at 2500 mg/m 2 combined with 50 mg/m 2 of cisplatin in NSCLC patients [14], indicates that higher gemcitabine doses could be safely used. Biweekly gemcitabine at doses of up to 3000 mg/m 2 has been used in combination with other agents, such as capecitabine, paclitaxel and vinorelbine [15,21,26].…”
Section: Treatment Details and Toxicity Analysissupporting
confidence: 57%
“…The G-CSF was administered on days 5-9. The dose of gemcitabine was based on the only data available at the time of the design of the study regarding the combination of high-dose gemcitabine with cisplatin [14]. This regimen resulted in a twofold increase in the DI of cisplatin and 1.66-fold increase of gemcitabine, compared with the standard GC [6].…”
Section: Selection and Randomizationmentioning
confidence: 99%
See 1 more Smart Citation
“…LopezVivanco et al [16] reported their experience with the biweekly administration of cisplatin and gemcitabine in the treatment of advanced NSCLC. The overall response rate was 38.8% and the median overall survival was 48 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Hematologic toxicity was less severe with a modified regimen employing a 3-week cycle with gemcitabine administration on d 1 and 8 [9][10][11][12][13] . In addition, both gemcitabine and cisplatin were given to patients with stage IIIB or IV NSCLC on the first day of every 2-week period [14] . However, the optimal schedule of combination chemotherapy with gemcitabine and cisplatin remains unknown.…”
Section: Introductionmentioning
confidence: 99%